THE DESIGN OF A PLURAL LAND USE PLANNIG SYSTEM - A TENTATIVE PROPOSAL FROM AN ITALIAN PERSPECTIVE - Sandro Fabbro (European Regional Science Association (ERSA), 2005)
The main approaches to planning developed during planning history are essentially three: the ritual one, the engineering one and the ethical one. With reference to the last category, classical ethical approaches to planning are those based on the principles of utilitarian (oriented to ensure efficiency and effectiveness for spatial changes), contractualist (oriented to pursue ends of social and environmental equity) and dialogical type (oriented to define planning ends in a public fair dialogue). But these ethical approaches seem inadequate, in their pure forms, to respond to policy-making requirements in our complex urban and regional societies. A really effective and fair system of spatial planning should instead respond not only to situations where ends and means are clear and well-defined but also to situations where there is strong conflict as regards the ends and to situations – perhaps the most frequent ones – where both ends and means are at the same time uncertain. From this standpoint it would seem that experiences (with particular reference to the Italian context) tending towards mixed and plural planning systems, should be regarded with interest. In this perspective, the contribution of the paper is finally addressed towards the definition of a mixed and plural, but loosely coupled, spatial planning system.
Keywords: 330